School culture and teacher efficacy as mediators in relationship between principals’ instructional leadership and school academic achievement in Malaysian secondary schools - Mohamad Yasin, Murni (2017)
The need for Malaysian student to register a high rating in the international assessment standards have created pressure on the nation and therefore demand schools and their principals to improve their schools’ outcomes. Many researchers have identified demographic, socio-economic status, family and school factors as variables contributing to school academic achievement. However, researchers also suggest that the principals who show leadership practices associated with the effective school models will have success in school academic achievement regardless of socioeconomic background. Schools can improve their learning outcomes regardless of initial achievement levels by changing key organizational aspects such as instructional leadership and teacher capacity. The purpose of this study was to examine the utility of three independent constructs which is instructional leadership, school culture, and teacher efficacy that is hypothesized to have significant effects on school academic achievement in secondary school of southern zone of Peninsular Malaysia, whether directly or indirectly. An extension of the research is to explore school culture and teacher efficacy as a potential mediator of the relationship between instructional leadership practices and school academic achievement. For the purpose of this study, a theoretical path mode to explain school academic achievement was developed with instructional leadership, school culture, and teacher efficacy as the key variables. Using structural equation modeling the hypothesized relationships were tested with data collected from 255 teachers from 16 secondary schools in southern zone of Peninsular Malaysia, as well as pre-existing school academic achievement data obtained from each school that participated. The findings provided substantial support for the model. Although the instructional leadership of the principal was not directly related to school academic achievement, it did have an indirect positive effect on school academic achievement through the school culture and teacher efficacy. In sum, this study adds to the understanding of the social system within the school that influences school academic achievement. Principal leadership can affect school academic achievement indirectly using their instructional leadership practices to build a healthy school culture and increase teacher efficacy with academic innovation and intellectual pursuits being the central focus of the school. Therefore, it is essential for instructional leadership components to be used in the curricular that effectively train new principals by Institute Aminuddin Baki.